Altered Proteolysis in Fibroblasts of Alzheimer Patients with Predictive Implications for Subjects at Risk of Disease. (18th May 2014) - Mocali, Alessandra; Della Malva, Nunzia; Abete, Claudia; Mitidieri Costanza, Vito Antonio; Bavazzano, Antonio; Boddi, Vieri; Sanchez, Luis; Dessì, Sandra; Pani, Alessandra; Paoletti, Francesco
Abstract : There is great interest in developing reliable biomarkers to support antemortem diagnosis of late-onset Alzheimer's disease (AD). Early prediction and diagnosis of AD might be improved by the detection of a proteolytic dysfunction in extracts from cultured AD fibroblasts, producing altered isoelectrophoretic forms of the enzyme transketolase (TK-alkaline bands). The TK profile and apolipoprotein E (APOE) genotype were examined in fibroblasts from 36 clinically diagnosed probable late-onset sporadic AD patients and 38 of their asymptomatic relatives, 29 elderly healthy individuals, 12 neurological non-AD patients, and 5 early-onset AD patients. TK alterations occurred in (i) several probable AD patients regardless of age-of-onset and severity of disease; (ii) all early-onset AD patients and APOE ε 4/4 carriers; and (iii) nearly half of asymptomatic AD relatives. Normal subjects and non-AD patients were all negative. Notably, culture conditions promoting TK alterations were also effective in increasing active BACE1 levels. Overall, the TK assay might represent a low-cost laboratory tool useful for supporting AD differential diagnosis and identifying asymptomatic subjects who are at greater risk of AD and who should enter a follow-up study. Moreover, the cultured fibroblasts were confirmed as a useful in vitro model for further studies on the pathogenetic process of AD.